2022
DOI: 10.1186/s12873-022-00623-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased ambulance on-scene times but unaffected response times during the first wave of the COVID-19 pandemic in Southern Denmark

Abstract: Background During the first wave of the COVID-19 pandemic, a lockdown was imposed on the Danish society. Reports from other countries that were hit by the COVID-19 pandemic before Denmark instilled fear of flooding of the emergency departments. To mitigate this flooding, increased competencies were conveyed to the paramedics in the ambulances aiming to allow for a release of a higher number of patients prehospitally. The increased competencies in the prehospital personnel were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
3
6
1
1
Order By: Relevance
“…The Delay time had no significant change before and during the COVID-19 pandemic. Eskol et al, Saffy et al, and Lim et al supported our study and indicated no significant changes in the lag time before and during the COVID-19 pandemic [ 17 19 ]. Since noisy phone line and the Internet interference often affected the lag time [ 20 ], the COVID-19 pandemic had no effect on the lag time in the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The Delay time had no significant change before and during the COVID-19 pandemic. Eskol et al, Saffy et al, and Lim et al supported our study and indicated no significant changes in the lag time before and during the COVID-19 pandemic [ 17 19 ]. Since noisy phone line and the Internet interference often affected the lag time [ 20 ], the COVID-19 pandemic had no effect on the lag time in the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results might be because patient triage in the emergency department had been longer during the COVID-19 pandemic (taking a history of the COVID-19 symptoms and examining the patients in terms of travel to suspected areas). Eskol et al (2020) compared the changes in the rate of EMS calls in southern Denmark before and during the COVID-19 pandemic but found no significant changes in the response time before and during the pandemic [ 17 ]. Moreover, Satty et al (2021) investigated emergency responses to non-traffic accidents during the COVID-19 pandemic in Pennsylvania, the United States and found no changes in the response time before and during the pandemic [ 18 ], so Eskol et al and Satty et al did not support our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an increase in the time required to visit the emergency room during COVID-19 [4,16], and consequently, patient prognoses for various diseases deteriorated [5,[16][17][18][19][20][21]. Further, delayed patient arrival time to the hospital worsened prognosis for diseases such as stroke, myocardial infarction, and cardiac arrest [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Stress in the work context of healthcare workers and thus also general stress tended to increase in the course of the pandemic, e.g., due to increased hygiene measures and concern about infections [24,27]. A study from Denmark showed longer operation times in prehospital operations and transport to the hospital, although the frequency of alarm operations decreased at the beginning of the pandemic [9]. All of this can have an additional impact on recovery and stress.…”
Section: Discussionmentioning
confidence: 99%